SOCIAL MEDIA ASSISTED LANGUAGE LEARNING (SMALL) FOR READING CLASSROOM : EFL LEARNERS’ PERCEPTION - Tarigan, Fatin Nadifa; Hasibuan, Siti Aminah; Nasution, Alwi Fahruzy (Universitas Pamulang, 2022)
Addressing the issue of the dynamics of social media as tool for learning, the present study aims at investigating the perception of English language learners towards the use of social media in the teaching learning activities especially for reading classroom. By using qualitative research, this study focuses on learner’s perceptions towards social media assisted for language learning (SMALL) in reading classroom. A total of 72 English language education learners at Universitas Pembinaan Masyarakat Indonesia participated in this study through 5 point Likert scale survey and interview. As the result, social media got positive perceptions from the learners. The dominant social media platform used was Instagram then following Youtube, Tiktok and Whatsapp. These learners believed that social media could be used as a tool for language learning that enhance learners' language skills especially reading and engage them better with lecturers and classmates in learning activities.